Endothelial cell loss after accelerated corneal crosslinking using pachymetry-guided hypo-osmolar riboflavin dosing in thin keratoconic corneas. Issue 12 (December 2021) - Yurttaser Ocak, Serap; Mangan, Mehmet Serhat
Abstract : Accelerated corneal crosslinking with only hypo-osmolar riboflavin solution throughout the procedure in thin corneas is effective but seems to result in a significant endothelial cell density decrease postoperatively. Abstract : Purpose: To report the intraoperative changes in corneal pachymetry, as well as the efficacy and safety of accelerated corneal crosslinking (A-CXL) treatment using only hypo-osmolar riboflavin (HO-RF) solution in progressive keratoconus patients with thin corneas. Setting: University of Health Sciences, Prof. Dr. Cemil Tascioglu Education and Research Hospital, Istanbul, Turkey Design: Retrospective study. Methods: Thin keratoconic corneas (<400 m without epithelium) who had A-CXL (9 mW/cm 2 -10 minutes) with HO-RF solution application were enrolled in the study. Intraoperative corneal pachymetric changes and uncorrected and corrected distance visual acuities (UDVA and CDVA), refraction power values, topographic values, and endothelial cell density (ECD) measurements were recorded preoperatively and at 1st, 3rd, 6th, and 12th month follow-up postoperatively. Results: 31 eyes of 25 patients (mean age: 24.17 ± 3.07 years) included in this study. The mean thickness increased to 438 μm ( P = .001) after the application of HO-RF solution, and it was reduced to 424 μm ( P = .001) after ultraviolet irradiation. At all postoperative visits after month 1, there was a significant increase in both UDVA ( P < .05) and CDVA ( P < .01) values and a significant decrease in both maximum keratometry ( P < .05) and ECD ( P < .01) values. Conclusions: Accelerated CXL with only HO-RF solution application throughout the procedure in thin corneas was effective but seemed to result in a significant ECD decrease postoperatively.